1994
DOI: 10.1139/b94-062
|View full text |Cite
|
Sign up to set email alerts
|

Seed yield and biomass allocation in Sorghum bicolor and F1 and backcross generations of S. bicolor × S. halepense hybrids

Abstract: The Land Institute is developing perennial grains to be grown in prairie-like mixtures. One approach involves the development of a perennial grain sorghum by crossing tetraploid Sorghum bicolor with wild S. halepense to combine high seed yield with overwintering ability via rhizome production. We grew tetraploid S. bicolor, F1 hybrid (BC0), and two backcross generations (BC1 and BC2) in a randomized block design to examine total biomass, seed yield, and allocation to plant parts within and across generations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
5
54
0
Order By: Relevance
“…Therefore, although leafy plants might have positive or no relationship between stem sugar and grain yield, the less leafy ones (at the same photosynthetic rates) tend to have a negative relationship between the two traits due to competition for the limited photo-assimilates. Piper and Kulakow (1994) reported that 42 to 74% of grain yield was attributed to plant biomass, results that are consistent with the positive and significant correlation coefficient between the two traits observed in the current study, although this is true only within a certain range after which the biomass start competing with the grain for photo-assimilates. The observed positive correlation coefficient between stem biomass and (i) head length, (ii) number of leaves per plant; (iii) plant height, and (iv) stem diameter (Table 3) could be attributed to the fact that plant height and stem diameter are major components contributing to the overall plant stem biomass.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, although leafy plants might have positive or no relationship between stem sugar and grain yield, the less leafy ones (at the same photosynthetic rates) tend to have a negative relationship between the two traits due to competition for the limited photo-assimilates. Piper and Kulakow (1994) reported that 42 to 74% of grain yield was attributed to plant biomass, results that are consistent with the positive and significant correlation coefficient between the two traits observed in the current study, although this is true only within a certain range after which the biomass start competing with the grain for photo-assimilates. The observed positive correlation coefficient between stem biomass and (i) head length, (ii) number of leaves per plant; (iii) plant height, and (iv) stem diameter (Table 3) could be attributed to the fact that plant height and stem diameter are major components contributing to the overall plant stem biomass.…”
Section: Discussionsupporting
confidence: 92%
“…The increased seed yield did not come at the expense of plant vigor or longevity. Piper and Kulakow (1994) found no correlation between seed and rhizome production in a population of unreplicated, winterhardy F3 plants from an interspecific cross between tetraploid Sorghum bicolor and S. halapense; however, rhizome production was all but lost in backcrosses to S. bicolor, the cultivated species.…”
Section: B Resource Allocation and Negative Correlationsmentioning
confidence: 85%
“…Hybrids between S. halapense and induced tetraploid lines of S. bicolor are easily made (Casaday and Anderson, 1952;Sanguden and Hanna, 1984;Piper and Kulakow, 1994). In an effort to produce a perennial grain sorghum at The Land Institute, Piper and Kulakow (1994) crossed S. halapense with tetraploid grain sorghum lines.…”
Section: Hybridization With Johnsongrassmentioning
confidence: 99%
See 2 more Smart Citations